A Robust Algorithm for Muscle Conduction Velocity Estimation - Wu, Patrick Chaoyu; Morin, Evelyn (CMBES Proceedings, 2017)
Muscle conduction velocity (CV) is used for detection of muscle fatigue and nerve malfunctioning, and for localization of the muscle innervation zone. Conventionally, CV is determined from the delay between two adjacent electromyogram (EMG) electrodes and the inter electrode distance (IED), i.e., CV=IED/delay. However, the accuracy of the CV estimate highly depends on the quality of the EMG signals. In this paper, a method to improve the robustness of the delay, and consequently the CV, estimate is developed and tested.